CAN THE '4 P'S OF PN' IMPROVE NEONATAL NUTRIENT INTAKE?. Issue 9 (17th August 2016) - Lansdowne, Zoe; Griffiths, Elizabeth
Abstract : Aims: ELBW infants on NICU were found to have poor growth compared to network data. Previous audit work1 showed that the time from birth to PN did not meet unit guideline targets and did not achieve optimal protein intake. Intensive work was done to publicise this and to decrease the time from birth to PN. Stock PN recipes were also reformulated to concentrate nutrition. The aim of audits 2 and 3 was to analyse whether publicising the 4 P's of PN (prompt, protein, protected and peripheral) could improve protein intake and ultimately increase growth velocity. Methods: The details of all infants born <28 weeks or <1 kg from 1st September to 30th November 2014 (audit 2) and from 1st April to 30th June 2015 (audit 3) were analysed retrospectively. Data was collected from the patients' medical notes, including parenteral nutrition (PN) prescriptions, fluid prescriptions and observation charts. Results: Over both 3 month audit cycles, data from a further 52 patients were analysed. It was found that the mean time from birth to PN for inborn infants was reduced from 10 hrs 59 mins to 7 hrs 14 mins, and then again further to 4 hrs 16 mins. On average all patients received more protein in the first 24 hrs of life in audit 3 compared to audits 2 and 1, 0.92 g/kg/day, 0.86 g/kg/day and 0.66 g/kg/day respectively. Just under 1/3 of patients achieved the target protein intake of 1.25 g/kg/day for day 1 of life in audit 3. For inborn patients only, protein intake increased from 0.83 g/kg/day to 1.09 g/kg/day to 1.38 g/kg/day over the audit cycle period. Inborn infants <750 g receiving PN within 6 hrs of birth increased from 17%, to 67%, and finally to 83% in audit 3. Of the infants still on the unit at day 14 of life, the mean daily protein intake increased from 2.15 g/kg/day to 2.35 g/kg/day and then to 2.46 g/kg/day, although the maximum achieved on a single day for a single infant was 3.87 g/kg/day, in audit 2. Average weight gain was 2.97 g/kg/day in audit 1 but this increased to over 7 g/kg/day in audits 2 and 3. All of the infants exceeded their birth weight by day 14 of life in audits 2 and 3, compared to only 71% in audit 1. The percentage of PN quantities prescribed but never administered remained constant between 13% and 16%. Conclusion: Publicising the 4 P's of PN ensured that PN was started promptly after birth resulting in increased protein intake on day 1 of life. Reformulating the stock PN bags to a more concentrated recipe, and protecting the PN volume infused, also increased protein intake. The results of these actions were improved growth velocity and all infants regained at least their birth weight by day 14 of life. Work still needs to be done to increase the mean daily protein intake. Peripheral PN was not actioned.